Hasil Skrining Perkembangan Anak Usia Toddler antara DDST dengan SDIDTK - Padila Padila; Fatsiwi Nunik Andari; Juli Andri (Jurnal Keperawatan Silampari, 2019)
The purpose of this study was to analyze the effectiveness of screening results for early detection of toddler age development between denver developmental screening test (DDST) interventions with stimulation, detection and early developmental intervention (SDIDTK). The research design used in this study is to use an experimental Quasy design, pre-post test equivalent without control group design. The results of univariate analysis before DDST intervention were 3 (30%) of the children whose stages of development were abnormal and doubtful and only 4 (40%) of the children were normal developmental stages, after the intervention, which were mostly 7 (70%) children whose stages of development are normal. While the results before SDIDTK intervention were 2 (20%) children whose developmental stages were abnormal and 4 (40%) of those children whose stages of development were normal and doubtful, after the intervention the majority were 7 (70%) children normal developmental stage. The results of bivariate analysis showed that there was an increase in the score of developmental stages in the DDST group and in the SDIDTK group with each (t value = -3.096, p value = 0.013) and (t value = -2.703, p value = 0.024). Conclusions of the results of the study there was a significant influence between the scores of the developmental stages in the DDST group and in the SDIDTKI group before and with after the intervention. Keywords: DDST II, ​​Development, SDIDTK, Screening, Toodler